2021
DOI: 10.1029/2020jc016751
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Variability and Transport in the Labrador Sea From In Situ and Satellite Observations

Abstract: The Labrador Sea off the southwest coast of Greenland plays an important role in the ocean circulation. The basin is a site of winter convection where the dense Labrador Sea Water is formed (Lazier, 1973;Pickart et al., 2002), and it is considered to be important for contributing to the cold limb of the meridional overturning circulation in the North Atlantic (Rhein et al., 2011). The Labrador Sea is also characterized by high biological activity, with highly productive phytoplankton blooms observed during spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
(118 reference statements)
1
9
0
Order By: Relevance
“…Therefore, it is characterized as the most significant exchange of the current system with the Labrador Sea interior, which is also shown by the observational study by Myers et al (2009). Majumder et al (2021) has also pointed out that the offshore transport from the coast to the interior Labrador Sea mainly occurs at 61°N-62°N. In terms of how the waters are transported offshore, besides predominantly offshore Ekman transports, Irminger Rings (Figure 1) are also formed and exchange waters offshore in this region (Katsman et al, 2004;Pennelly & Myers, 2022).…”
Section: Transport Losses and Exchangessupporting
confidence: 53%
See 4 more Smart Citations
“…Therefore, it is characterized as the most significant exchange of the current system with the Labrador Sea interior, which is also shown by the observational study by Myers et al (2009). Majumder et al (2021) has also pointed out that the offshore transport from the coast to the interior Labrador Sea mainly occurs at 61°N-62°N. In terms of how the waters are transported offshore, besides predominantly offshore Ekman transports, Irminger Rings (Figure 1) are also formed and exchange waters offshore in this region (Katsman et al, 2004;Pennelly & Myers, 2022).…”
Section: Transport Losses and Exchangessupporting
confidence: 53%
“…And a recent observational study by Majumder et al. (2021) has shown that the speed of the WGC flowing from 61°N to 64–65°N is approximately 0.17 ms −1 .…”
Section: Speedsmentioning
confidence: 95%
See 3 more Smart Citations